Pelatihan Caregiver Lansia tentang Tatalaksana Awal pada Kondisi Pingsan dan Serangan Stroke - Ellia Ariesti; Elizabeth Yun Yun Vinsur; Narita Diatanti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: The community partnership program activity "Training for Elderly Caregivers on Initial Management in Syncope Conditions and Stroke Attacks at LKS-LU Pangesti Lawang" is an activity intended for elderly caregivers who are responsible for the health of the elderly at LKS-LU Pangesti Lawang. Objective: The purpose of this community partnership program is to facilitate elderly caregivers in carrying out initial management of syncope conditions and stroke attacks at LKS-LU Pangesti Lawang. Considering that the elderly are a special group that is vulnerable and at risk of experiencing various problems related to their health. Decreased physical, mental and social abilities have health impacts and risks for various neurovascular diseases. Method: This training was carried out in the form of: Providing education and sharing about physiological changes in the elderly, especially about changes in the cardiovascular systems and neurovascular systems as well as providing education and training on early management in syncope conditions and stroke attacks. Result: The implementation of activity with the title "Elderly Caregiver Training on Early Management in Syncope Conditions and Stroke Attacks at LKS-LU Pangesti Lawang" went well and smoothly. The activity was carried out with a 100% participant attendance rate. The material on Initial management of Syncope and Stroke Attacks has been delivered according to the topic by the speakers and the active participants in the discussion carried out. The indicator of the success of this activity is from the results of the evaluation on the participants when the training was carried out, most of the participants were able to answer pre and posttest questions and demonstrations. The results obtained were as follows, the average score of the participants' pretests was 64, and the average score of posttests was 70. Average scores of initial management practices in syncope conditions and strokes with good results. Conclusion: On this basis, it can also be concluded that the purpose of training that wants to increase the knowledge and understanding of health cadres regarding Early Management in Syncope Conditions and Stroke Attacks in LKS-LU Pangesti Lawang has been achieved.